STRATEGY FOR STRENGTHENING THE INSTITUTION OF WOMEN'S FARMING GROUPS IN AN EFFORT TO SUPPORT FAMILY FOOD INDEPENDENCE IN KALIMANAH DISTRICT PURBALINGGA REGENCY - Tutut Dwi Purwani; Tyas Retno Wulan; Hariyadi (CV. Radja Publika, 2025)
The Women Farmers Group (KWT) is a forum for women to participate in advancing the agricultural sector, encouraging innovation, economic independence, and improving the welfare of families and communities. KWT plays a strategic role in supporting family food independence while strengthening national food security. However, not all KWTs have strong and sustainable institutions. This study aims to map the institutional conditions of KWT and formulate institutional strengthening strategies in an effort to support family food independence in Kalimanah District, Purbalingga Regency. The study uses a qualitative approach with data collection techniques through in-depth interviews, direct observation, Focus Group Discussion (FGD), and document study. Informants were determined using purposive sampling by selecting three KWTs that represent different institutional conditions, namely KWT Aglonema (advanced), KWT Sri Lestari (developing), and KWT Melati (declining). Data analysis was conducted using a SWOT approach combined with Richard Scott's institutional theory, which includes regulatory, normative, and cognitive pillars. The results showed that the institutional conditions of KWTs in Kalimanah Subdistrict varied, influenced by leadership, member participation, internal rules, and external support. Institutional strengthening strategies were directed at increasing human resource capacity, strengthening organizational systems, partnerships, diversifying yard-based food activities, and optimizing the role of agricultural extension workers. Sustainable institutional strengthening of KWT is expected to increase the role of women farmers in achieving family food self-sufficiency.